Circulation of bluetongue virus 8 in French cattle, before and after the re‐emergence in 2015. Issue 1 (2nd May 2017) - Courtejoie, N.; Durand, B.; Bournez, L.; Gorlier, A.; Bréard, E.; Sailleau, C.; Vitour, D.; Zientara, S.; Baurier, F.; Gourmelen, C.; Benoit, F.; Achour, H.; et al.
Summary: Bluetongue virus serotype 8 (BTV‐8) re‐emerged in Central France in August 2015. The viral strain identified is nearly identical to the one that circulated during the 2006/2009 massive outbreak throughout Europe. To address the question of an undetected BTV‐8 circulation on the French territory, a serological study was conducted on young cattle along a transect of seven departments, three of them located in areas where the virus presence had been confirmed by RT‐PCR by winter 2015/2016. Sera from 2, 565 animals were collected during the winters preceding and following the re‐emergence, with 414 animals being sampled in each of the two consecutive years. All samples were tested by competitive ELISA (IDVet) and, when enough serum was available, ELISA‐positive samples were confirmed by seroneutralization tests. In areas with infected holdings, seropositive animals were found before the re‐emergence ( N = 14 of 511), significantly more on the following year ( N = 17 of 257), and eight animals ( N = 158) seroconverted over 2015. Seropositive animals were also detected as early as winter 2014/2015 in one department without known infected holdings ( N = 12 of 150), and in winter 2015/2016 in three of them ( N = 21 of 555), where seven animals ( N = 154) seroconverted over 2015. These results suggest that BTV‐8 may have spread at low levels before the re‐emergence, even in areas considered virus‐free. Unfortunately, whole blood from the seropositive animals was not available to definitely confirm the virus presence by RT‐PCR.